Design of planar microcoil-based NMR probe ensuring high SNR - Ali, Zishan (2019)
A microNMR probe for ex vivo applications may consist of at least one microcoil, which can be used as the oscillating magnetic field (MF) generator as well as receiver coil, and a sample holder, with a volume in the range of nanoliters to micro-liters, placed near the microcoil. The Signal-to-Noise ratio (SNR) of such a probe is, however, dependent not only on its design but also on the measurement setup, and the measured sample. This paper introduces a performance factor P independent of both the proton spin density in the sample and the external DC magnetic field, and which can thus assess the performance of the probe alone. First, two of the components of the P factor (inhomogeneity factor K and filling factor η) are defined and an approach to calculate their values for different probe variants from electromagnetic simulations is devised. A criterion based on dominant component of the magnetic field is then formulated to help designers optimize the sample volume which also affects the performance of the probe, in order to obtain the best SNR for a given planar microcoil. Finally, the P factor values are compared between different planar microcoils with different number of turns and conductor aspect ratios, and planar microcoils are also compared with conventional solenoids. These comparisons highlight which microcoil geometry-sample volume combination will ensure a high SNR under any external setup.